Visual Perturbation Suggests Increased Effort to Maintain Balance in Early Stages of Parkinson’s to be an Effect of Age Rather Than Disease - Student, Justus; Engel, David; Timmermann, Lars; Bremmer, Frank; Waldthaler, Josefine (Frontiers in Human Neuroscience, 2022)
Postural instability marks a prevalent symptom of Parkinson’s disease (PD). It often manifests in increased body sway, which is commonly assessed by tracking the Center of Pressure (CoP). Yet, in terms of postural control the body’s Centre of Mass (CoM) is what is regulated in a gravitational field, and not the CoP. To find potential biomarkers of subclinical alterations of early-stage PD regarding postural control, we determined CoP and CoM in response to unpredictable visual perturbations. We investigated three different cohorts: (i) 18 patients with early to mid-stage PD, (ii) a group of 15 age-matched controls (CT) and (iii) a group of 12 young healthy adults (YG). Participants stood on a force plate to track their CoP, while movement of their entire body was recorded with a video-based motion tracking system to monitor their CoM. A moving room paradigm was applied through a head-mounted virtual reality headset. The stimulus consisted of a virtual tunnel that stretched in the anterior-posterior direction. The tunnel either remained static or moved back and forth in an unpredictable fashion. We found differences in mean velocities of CoP and CoM between the groups under both conditions with higher velocities of CoP and CoM for PD and CT when compared to YG. Visual perturbation increased mean CoP velocity in all groups, but only had a slight effect on mean CoM velocity. While being significantly lower for the young adults, the net-effect of visual perturbation on mean CoP velocity was similar between patients with PD and age-matched controls. There was no effect of the perturbation on mean CoM velocity for any of the groups. Our simultaneous assessment of CoP and CoM revealed that postural control is reflected differently in CoM and CoP. As motion of the CoM remained mostly unaffected, all groups successfully counteracted the perturbation and maintained their balance. Higher CoP velocity for PD and CT revealed increased corrective motion needed to achieve this successful behavior, which however was similar in both groups. This suggests increased effort, expressed in CoP velocity, to be an effect of age rather than disease in earlier stages of PD.